Modelling the impact of heavy work investments on employee's satisfaction - Mihail Busu; Attila Gyorgy (Amfiteatru Economic Journal, 2020)
In this article, the authors develop an econometric model to determine the impact of the heavy work investment on employee's satisfaction. The data was collected using a questionnaire addressed to employees with higher level of education and at least one year of experience, within the specialized departments of multinational companies that offer consultancy and audit services in Romania and analyzed using Smart-Pls statistical software 3.3.2. Based on the literature in the field, the article identifies the determinants of the heavy work investment. These indicators are the independent variables that shape the impact of the heavy work investment on employee's performance and satisfaction. The findings confirm the theoretical aspects presented in the article, emphasizing that employee's satisfaction is the direct result of the collaboration of several factors, such as personal needs, workload, time spent at work, attitude to work and physical and mental condition. Identifying the drivers that contribute to increasing organizational performance is essential in the human resources management process, to shed light on positive aspects, such as employee satisfaction, rewarded for their work and, at the same time, to prevent the risk of overwork. The article contributes to the research theory by modelling the investment in work according to elements specific to human typologies, bringing a unique contribution in the form of practical inferences for the management of human resources.
Keywords: O12; O15; C30; C83; 330; heavy work investment; work satisfaction; work dependence; econometric model; PLS-SEM